The Forager Oral Tradition and the Evolution of Prolonged Juvenility - Scalise Sugiyama, Michelle (Frontiers in Psychology, 2011)
The foraging niche is characterized by the exploitation of nutrient-rich resources using complex extraction techniques that take a long time to acquire. This costly period of development is supported by intensive parental investment. Although human life history theory tends to characterize this investment in terms of food and care, ethnographic research on foraging skill transmission suggests that the flow of resources from old to young also includes knowledge. Given the adaptive value of information, parents may have been under selection pressure to invest knowledge—e.g., warnings, advice--in children: proactive provisioning of reliable information would have increased offspring survival rates and, hence, parental fitness. One way that foragers acquire subsistence knowledge is through symbolic communication, including narrative. Tellingly, oral traditions are characterized by an old-to-young transmission pattern, which suggests that, in forager groups, storytelling might be an important means by which adults transfer knowledge to juveniles. In particular, by providing juveniles with vicarious experience, storytelling may expand episodic memory, which is believed to be integral to the generation of possible future scenarios (i.e., planning). In support of this hypothesis, this essay reviews evidence that: mastery of foraging knowledge and skill sets takes a long time to acquire; foraging knowledge is transmitted from parent to child; the human mind contains adaptations specific to social learning; full assembly of learning mechanisms is not complete in early childhood; and forager oral traditions contain a wide range of information integral to occupation of the foraging niche. It concludes with suggestions for tests of the proposed hypothesis.